Menjelajahi Ilmu Manajemen Generasi Ke 5 (Brainware Management) Menuju Kualitas Ilmu Manajemen Terintegrasi Dengan Posmodernisme - Adang Adang; Dedi Hadian (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2018)
The age of postmodernism is part of the rejection of the paradigm of Rene Descrates through Cartesian - Newtonian jargon. This region rarely gets attention in the field of science / management flow in Indonesia. The conceptualization of management science in Indonesia tends to be quantified by statistical and mathematical formulas. The pioneers of this science forget Peter Drucker who introduced the